Low-warping microcrystalline glass, preparation method thereof, glass device, cover plate glass and electronic equipment
Patent Information
- Application Number
- CN202610779136.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2026-06-02
- Publication Date
- 2026-08-28
- Estimated Expiration
- 2046-06-02
AI Technical Summary
[0006]本发明的目的在于提供一种低翘曲微晶玻璃及其制备方法,玻璃器件、盖板玻璃和电子设备,以解决现有玻璃制品在堆叠晶化过程中由于热传导不均、界面粘连及局部结晶差异所导致的翘曲增大、结晶均匀性不足以及后续加工适配性差的问题
第一,本发明通过在制造过程中引入石墨/二氧化硅复合功能层,能够显著改善堆叠结构内部的热场均匀性,从而有效降低晶化过程中产生的翘曲,获得低翘曲玻璃制品。
Smart Images

Figure CN122325111B_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of glass and ceramic manufacturing, specifically relating to a low-warpage microcrystalline glass and its preparation method, glass devices, cover glass, and electronic devices. Background Technology
[0002] As electronic terminals, automotive displays, and wearable devices develop towards thinner, larger, and more reliable designs, glass products, especially glass-ceramic materials, are widely used in display covers, touch panels, and structural components due to their excellent mechanical properties, dimensional stability, and optical properties.
[0003] In the fabrication of glass-ceramic products, glass substrates typically undergo nucleation and crystallization heat treatment to transform them into glass-ceramic materials with specific crystalline phase structures. To improve production efficiency, multiple glass substrates are usually stacked and crystallized together. However, during the stacking crystallization process, due to interfacial interactions between adjacent glass substrates and uneven heat conduction, temperature distribution differences can easily occur in different regions, leading to inconsistent crystallization rates. This ultimately results in significant warpage and poor crystallization uniformity in the glass products. For glass products used in display cover plates and other applications, warpage is a key indicator affecting dimensional accuracy, assembly yield, and subsequent processing stability, especially with the trend towards larger sizes or thinner profiles, where warpage becomes more pronounced. Furthermore, insufficient crystallization uniformity can also lead to uneven distribution of material properties, thus affecting subsequent machining performance and strengthening effects.
[0004] In existing technologies, although the adhesion can be reduced and the stacking state improved by setting isolation materials or functional layers between glass substrates, these solutions mainly focus on interface separation and have limited ability to control the overall thermal field distribution during crystallization. This makes it difficult to fundamentally solve the warping and crystallization differences caused by uneven heat conduction. Furthermore, for high-precision glass products requiring CNC machining, polishing, and chemical strengthening, if the functional materials introduced during crystallization remain on the product surface for a long period, it may adversely affect the quality of subsequent processing.
[0005] Therefore, how to effectively control the thermal conductivity between glass substrates during crystallization without affecting subsequent processing and performance, reduce warpage and improve crystallization uniformity, so as to obtain low-warpage glass products suitable for high-precision processing, remains a technical problem that urgently needs to be solved in this field. Summary of the Invention
[0006] The purpose of this invention is to provide a low-warpage microcrystalline glass and its preparation method, as well as glass devices, cover glass and electronic devices, to solve the problems of increased warpage, insufficient crystallization uniformity and poor adaptability to subsequent processing caused by uneven heat conduction, interface adhesion and local crystallization differences in existing glass products during the stacking crystallization process.
[0007] This invention provides a method for preparing low-warpage microcrystalline glass, comprising the following steps: Step 1: Melting. Weigh out the following components by mass fraction: SiO2 60-75%, Al2O3 2-5.5%, P2O5 2-5%, Li2O 10-18%, ZrO2 4-10%, CaO 0-1%, Na2O 0-1.5%, Sb2O3 0.02-0.6%, SnO2 0.2-0.6%. Mix them evenly, melt them into a mold, and then anneal them to obtain a glass substrate. Step 2: Coating. A composite functional layer is formed on at least one main surface of the glass substrate obtained in Step 1. The composite functional layer is formed on the main surface of the glass substrate by spraying, controlling the coating uniformity deviation to ≤5%. After drying, the composite functional layer is formed. Here, for general objects, the main surface refers to the outer surface (or two) with the largest area. For glass substrates, it refers to the two planes on the top and bottom with areas much larger than the sides.
[0008] Step 3: Crystallization. The glass substrates with composite functional layers obtained in Step 2 are stacked and placed in a box furnace. First, the temperature is increased to 540℃-620℃ at a rate of 1℃ / min-5℃ / min and held for 1h-10h for nucleation treatment. Then, the temperature is increased to 640℃-780℃ at a rate of 1℃ / min-3℃ / min and held for 0.5h-5h for crystallization treatment. Finally, the temperature is cooled to room temperature at a rate of 3℃ / min-10℃ / min to complete the crystallization treatment and obtain a glass microcrystalline glass stack. Step 4: Destabilize and process the glass stacks by manually or mechanically separating them. Perform CNC machining and polishing on the glass to obtain low-warpage glass products.
[0009] Furthermore, the composite functional layer in step 2 consists of graphite particles, silica particles, and a dispersant, wherein the mass ratio of graphite particles to silica particles is (2-6):5, and the content of the dispersant is 0.249-2.59 wt% of the total weight of the composite functional layer.
[0010] Preferably, the graphite particles are flake graphite particles with an average particle size of 1μm-10μm and a degree of graphitization of not less than 85%; the silica particles are amorphous silica particles with a particle size of 100nm-5μm; and the dispersant is sodium hydroxide and / or potassium hydroxide.
[0011] Preferably, the method for preparing low-warp microcrystalline glass further includes step 5: subjecting the obtained glass product to ion exchange treatment and then polishing it.
[0012] A low-warpage microcrystalline glass, prepared by the aforementioned method, has a warpage ≤1.5μm / mm and a crystallinity difference of ≤5% at five points.
[0013] Furthermore, the crystalline phase of the low-warp glass-ceramic contains lithium disilicate, or lithium disilicate and lithium feldspar, and the crystalline phase accounts for 60%-90% of the weight of the glass-ceramic.
[0014] Furthermore, this invention also aims to provide a temporary composite functional layer suitable for the glass substrate stacking crystallization process and its application. This composite functional layer exists and functions only during the crystallization process, regulating the interface state and thermal conductivity between adjacent glass substrates, thereby reducing warping caused by the crystallization process and improving crystallization uniformity. After crystallization is completed, the composite functional layer is removed by a subsequent polishing process, or no longer constitutes an effective surface structure of the final glass product, and therefore is not retained as a long-term surface coating of the final product.
[0015] The second technical solution of the present invention is to provide a low-warpage microcrystalline glass, wherein the low-warpage microcrystalline glass is a microcrystalline glass product obtained by crystallization treatment and subsequent surface processing. The microcrystalline glass product includes a glass-ceramic matrix, wherein the glass-ceramic matrix comprises one or more crystalline phases and a residual glass phase.
[0016] In some embodiments, the crystalline phase of the low-warp microcrystalline glass comprises lithium disilicate or lithium disilicate / lithium feldspar. Preferably, the crystalline phase accounts for 60-90% of the weight of the glass-ceramic matrix. By controlling the glass composition and crystallization regime, the resulting glass products can possess good mechanical properties, optical properties, and dimensional stability.
[0017] In some embodiments, the low-warp microcrystalline glass comprises, by mass percentage of oxides: 60-75% SiO2, 2-5.5% Al2O3, 2-5% P2O5, 10-18% Li2O, 5-15% ZrO2, 0-1% CaO, 0-1.5% Na2O, 0.02-0.6% Sb2O3, and 0.2-0.6% SnO2.
[0018] In some embodiments, the low-warpage microcrystalline glass meets at least one or more of the following performance characteristics: warpage not greater than 1.5 μm / mm; crystallinity difference at five points not greater than 5%. These performance indicators reflect the comprehensive improvement in dimensional stability and crystallinity uniformity of the glass products of the present invention, making them particularly suitable for display cover plates and protective components where flatness and structural consistency are highly required.
[0019] The preferred dimensions of the low-warp microcrystalline glass are 161.6 mm in length × 76.3 mm in width and 0.4-0.8 mm in thickness.
[0020] The present invention also provides a method for preparing the above-mentioned low-warpage glass article, the method comprising the following steps: Step 1: Melting. Weigh out the following components by mass fraction: SiO2 60-75%, Al2O3 2-5.5%, P2O5 2-5%, Li2O 10-18%, ZrO2 4-10%, CaO 0-1%, Na2O 0-1.5%, Sb2O3 0.02-0.6%, and SnO2 0.2-0.6%. Mix them evenly, melt them into a mold, and then anneal them to obtain a glass substrate. The melting temperature is 1400 ℃-1600 ℃, and the melting time is 6 h-10 h. The preheating temperature of the stainless steel mold is 300 ℃-450 ℃. The annealing temperature is 400 ℃-500 ℃, and the annealing time is 3 h-6 h.
[0021] Step 2: Coating, forming a composite functional layer on at least one main surface of the glass substrate. Preferably, the composite functional layer is formed on the upper main surface of the glass substrate by spraying, controlling the coating uniformity deviation to ≤5%, and then forming a stable structure after drying; preferably, the composite functional layer is applied to one side. Using a single-side application method ensures an effective isolation interface between adjacent glass substrates during stacking, and reduces unnecessary material introduction, facilitating subsequent processing. Preferably, the slurry composition during spraying in this step consists of graphite particles, silica particles, dispersant, and the remainder water, wherein the silica particle content is 20%-50% of the total slurry content, the graphite particle content is 10%-30% of the total slurry content, and the dispersant content is 0.2-0.8% of the total slurry content. Step 3: Crystallization. The glass stack is placed in a box furnace and heated to 540℃-620℃ at a rate of 1℃ / min-5℃ / min, and held for 1h-10h for nucleation. Then, the temperature is increased to 640℃-780℃ at a rate of 1℃ / min-3℃ / min, and held for 0.5h-5h for crystallization. Finally, the temperature is cooled to room temperature at a rate of 3℃ / min-10℃ / min to complete the crystallization process and obtain the glass microcrystalline glass stack.
[0022] Step 4: Destacking and processing. Due to the isolation effect of the composite functional layer, there is no adhesion between the glass sheets in the glass stack, and they can be separated directly by manual or mechanical means. The glass is then CNC machined and polished to obtain low-warpage glass products. Further, the obtained glass products undergo ion exchange treatment and are then repolished to obtain high-strength, low-warpage microcrystalline glass.
[0023] The drying process in step 2 involves placing the coated glass substrate in a drying device and drying it at 60 ℃-120 ℃ for 15 min-45 min to remove moisture and form a stable composite functional layer, thus obtaining a glass substrate with a composite functional layer.
[0024] The stacking in step 2 involves stacking 5-15 glass substrates with composite functional layers, stacking adjacent glass substrates so that the composite functional surface of one substrate contacts the non-functional surface of the other, forming a glass stack. A backing plate is placed at the top and bottom of the glass stack. The backing plate is made of silicon carbide material that does not react with the glass ceramic composition. The surface of the backing plate that contacts the glass product can be selectively coated with a functional layer to further prevent adhesion.
[0025] In step 3, during the crystallization process, the graphite / silica composite functional layer not only prevents adjacent glass substrates from sticking together, but more importantly, it synergistically improves the uniformity of the thermal field within the stack by adjusting the heat conduction path through graphite particles and stabilizing the interfacial isolation state through silica particles. The inventors believe that because the thermal field distribution within the stack is more uniform, the crystallization process in different regions of the glass substrate becomes more consistent, resulting in the final glass product exhibiting lower warpage and smaller five-point crystallinity differences. Therefore, the technical problem solved by this invention is not only the interfacial demolding problem, but also the problem of preparing low-warpage glass products.
[0026] In some embodiments, the graphite particles are flake graphite particles with an average particle size of 1 μm-10 μm and a graphitization degree of not less than 85%. The introduction of graphite particles is not simply to replace existing insulating materials, but to utilize their good thermal conductivity and interfacial lubrication to improve the thermal field uniformity during crystallization and reduce interfacial friction. If there are too few graphite particles, the heat conduction homogenization effect is insufficient, making it difficult to significantly reduce warpage; if there are too many graphite particles, it may lead to coarsening of the layered structure, decreased coating stability, or poor surface uniformity, thus hindering the achievement of a stable low warpage effect.
[0027] In some embodiments, the silica particles are amorphous silica particles, preferably amorphous silica aggregates, with an average particle size of 100 nm-5 μm. The silica particles primarily serve to provide compatibility with the glass substrate and form a stable insulating interface during the stacking and crystallization process, reducing the risk of adhesion and adverse interfacial reactions between the glass substrates. Compared to graphite particles, silica particles place greater emphasis on isolation and compatibility functions.
[0028] In some embodiments, the mass ratio of graphite particles to silica particles is 2:5-6:5. Preferably, graphite particles account for 10%-30% of the total solid content of the slurry, and silica particles account for 20%-50% of the total solid content of the slurry. Within the scope required by the present invention, graphite and silica can work synergistically to achieve a better balance between warpage, five-point crystallinity difference, and separation effect in the resulting glass product; when the graphite content is too low or too high, the relevant properties will deteriorate significantly. In some embodiments, the mass ratio of graphite particles to silica particles is 0.4 or 0.45 or 0.5 or 0.55 or 0.6 or 0.65 or 0.7 or 0.75 or 0.8 or 0.85 or 0.9 or 0.95 or 1 or 1.05 or 1.1 or 1.05 or 1.2 or any value between the two aforementioned values.
[0029] In some embodiments, the dispersant is selected from at least one of sodium hydroxide and potassium hydroxide. The dispersant is used to improve the dispersion stability of graphite particles and silica particles in an aqueous system and facilitates the formation of a uniform composite functional layer. Preferably, the dispersant content is 0.2%-0.8% of the total weight of the slurry, the slurry pH is 8.5-11, and the slurry viscosity is 35 cp-75 cp. Under the above-mentioned alkaline dispersion system, particle dispersibility, spray uniformity, and coating stability can be balanced. Compared with acidic dispersion systems, the alkaline system is more conducive to obtaining lower warpage and smaller crystallinity differences.
[0030] In some embodiments, the average dry weight coverage of the composite functional layer is 0.4 g / m²-1.6 g / m², and the preferred average thickness is 1 μm-5.5 μm. If the coverage is too low, the interface isolation and thermal regulation effects are insufficient; if the coverage is too high, it may increase the inhomogeneity of the layered structure, affecting the stability of the stacked interface and the ease of subsequent processing.
[0031] Compared to a single silica system, the use of a graphite / silica composite functional layer further reduces the warpage and five-point crystallinity difference in the resulting glass products. While a single silica system primarily focuses on interfacial isolation and compatibility, this invention, by introducing graphite particles, maintains interfacial isolation while actively regulating the thermal conductivity during crystallization, achieving superior results in low warpage and uniform crystallization.
[0032] Composition description of low warp glass products: SiO2 (silicon dioxide), as the forming oxide of the glass network, provides the structural framework. Appropriately increasing the SiO2 content can enhance the stability and mechanical strength of the glass, facilitating the precipitation of the desired amount of lithium disilicate crystalline phase. However, excessive SiO2 increases the viscosity of the substrate glass, making glass melting more difficult and reducing the formability of the substrate glass; too little SiO2 leads to a loose network structure, reducing the hardness and impact resistance of the glass. Therefore, the SiO2 content in this invention is 60-75 wt%, preferably 65-75 wt%. In some embodiments, the SiO2 content is 60 wt%, 61 wt%, 62 wt%, 63 wt%, 64 wt%, 65 wt%, 66 wt%, 67 wt%, 68 wt%, 69 wt%, 70 wt%, 71 wt%, 72 wt%, 73 wt%, 74 wt%, 75 wt%, or any value between the aforementioned two values.
[0033] Al2O3 (alumina), as a network intermediate, can replace some SiO2 in the glass network, filling network voids and improving mechanical strength and chemical stability. Too low an Al2O3 content is detrimental to crystal precipitation and affects mechanical properties; too high a content will increase glass viscosity and cause other crystalline phases to precipitate, affecting the optical and mechanical properties of the glass material. Therefore, the Al2O3 content in this invention is 2-5.5 wt%, preferably 2.5-5.5 wt%. In some embodiments, the Al2O3 content is 2.5 wt%, 3 wt%, 3.5 wt%, 4 wt%, 4.5 wt%, 5 wt%, 5.5 wt%, or any value between the aforementioned two values.
[0034] P2O5 (phosphorus pentoxide), as a forming oxide, can promote uniform nucleation and refine grain size. If the P2O5 content is too low, it cannot provide sufficient nucleation sites, causing the glass system to tend to precipitate lithium metasilicate crystals. If the P2O5 content is too high, the precipitated grains will be too large, affecting light transmittance. Therefore, the P2O5 content in this invention is 2-5 wt%, preferably 2-4 wt%. In some embodiments, the P2O5 content is 2 wt%, 2.5 wt%, 3 wt%, 3.5 wt%, 4 wt%, 4.5 wt%, 5 wt%, or any value between the aforementioned two values.
[0035] Li₂O (lithium oxide), as a network oxide, not only improves the viscosity of glass and promotes the melting and clarification of molten glass, but is also one of the main components in the formation of lithium disilicate crystals, increasing the elastic modulus, hardness, and scratch resistance. Too low a content results in insufficient crystal phase precipitation, affecting the strengthening effect; too high a content easily leads to excessive crystallization, affecting forming and optical properties. Therefore, the Li₂O content in this invention is 10-18 wt%, preferably 10-16 wt%. In some embodiments, the Li₂O content is 10 wt%, 10.5 wt%, 11 wt%, 11.5 wt%, 12 wt%, 12.5 wt%, 13 wt%, 13.5 wt%, 14 wt%, 14.5 wt%, 15 wt%, 15.5 wt%, 16 wt%, 16.5 wt%, 17 wt%, 17.5 wt%, 18 wt%, or any value between the aforementioned two values.
[0036] Zirconia (ZrO2) serves as an intermediate oxide and a highly efficient nucleating agent. Appropriate amounts of ZrO can optimize crystal size and distribution, significantly improving the chemical stability and mechanical strength of the glass. However, excessive ZrO content can drastically increase the viscosity of the glass melt, making it difficult to remove bubbles and affecting product yield. It can also easily lead to excessive crystallization and low transmittance. Therefore, the ZrO2 content in this invention is 4-10 wt%, preferably 6-10 wt%. In some embodiments, the ZrO2 content is 4 wt%, 4.5 wt%, 5 wt%, 5.5 wt%, 6 wt%, 6.5 wt%, 7 wt%, 7.5 wt%, 8 wt%, 8.5 wt%, 9 wt%, 9.5 wt%, 10 wt%, or any value between the aforementioned two.
[0037] CaO (calcium oxide), as a network oxide, helps reduce the high-temperature viscosity of glass and increase its density when used in appropriate amounts. However, excessive CaO shortens the glass's thickness, increases its brittleness, and easily leads to crystallization, affecting its optical properties. Therefore, the CaO content in this invention is 0-1 wt%, preferably 0-0.8 wt%.
[0038] Sodium oxide (Na₂O) acts as a network oxide. Appropriate amounts of Na₂O can provide free oxygen, improve the viscosity of the glass, promote the melting and clarification of the molten glass, and regulate the chemical strengthening rate. Excessive Na₂O, however, increases the coefficient of thermal expansion of the glass and reduces its thermal stability. Therefore, the Na₂O content in this invention is 0-1.5 wt%, preferably 0-1.2 wt%.
[0039] Sb₂O₃ and SnO₂ are used as clarifying agents to remove bubbles during the glass melting process, thereby improving glass quality. Appropriate addition does not affect chemical stability. In this invention, the upper limit of the content of both SnO₂ and Sb₂O₃ is set at 0.6 wt%.
[0040] Based on the above technical solution, the present invention has at least the following beneficial effects: First, by introducing a graphite / silicon dioxide composite functional layer during the manufacturing process, the present invention can significantly improve the thermal field uniformity inside the stacked structure, thereby effectively reducing the warpage generated during crystallization and obtaining low-warpage glass products.
[0041] Secondly, the present invention can reduce the crystallinity difference between different regions of glass products, improve the consistency of material structure and performance stability, and is especially beneficial to the stable implementation of subsequent finishing processes.
[0042] Third, the composite functional layer in this invention is only a temporary functional layer in the crystallization process and does not exist as a permanent surface structure of the final glass product. Therefore, it can play a regulatory role in the crystallization process without adversely affecting the surface structure of the final product and its adaptability to post-processing.
[0043] Fourth, this invention achieves a combination of interface isolation, thermal conduction regulation, and ease of separation through the synergistic effect of graphite particles and silica particles. Unlike single material systems that are only optimized for interface separation, this invention has a more outstanding comprehensive effect.
[0044] Fifth, the low-warp glass products obtained by this invention can be widely used in electronic terminal display covers, vehicle display protective components, and other high-precision glass components that require polishing. Attached Figure Description
[0045] Figure 1 This is a five-point crystallinity difference diagram of the glass obtained in Example 1 of the present invention; Figure 2 This is a five-point crystallinity difference diagram of the glass obtained in Example 6 of the present invention; Figure 3 This is a photograph of the glass produced in embodiment 5 of the present invention; Figure 4 This is a photograph of the glass produced in Comparative Example 6 of this invention. Figure 5 This is a photograph of the glass produced in Comparative Example 7 of this invention. Detailed Implementation
[0046] To further clarify and illustrate the technical solution of the present invention, the following non-limiting embodiments are provided. While the embodiments of the present invention have made considerable efforts to ensure numerical accuracy, some errors and deviations must be taken into account. The components themselves are given as mass fractions (%) and have been standardized to 100%.
[0047] The technical solution and its beneficial effects of the present invention will be further described below with reference to embodiments and comparative examples. However, it should be understood that these embodiments are only for illustrating the present invention and are not intended to limit the scope of protection of the present invention. For those skilled in the art, various modifications and substitutions made without departing from the concept of the present invention should fall within the scope of protection of the present invention.
[0048] The glass substrate used in the embodiments and comparative examples of this invention comprises, by mass percentage of oxides: 60-75% SiO2, 2-5.5% Al2O3, 2-5% P2O5, 10-18% Li2O, 4-10% ZrO2, 0-1% CaO, 0-1.5% Na2O, 0.02-0.6% Sb2O3, and 0.2-0.6% SnO2. The substrate is uniformly mixed, melted, and annealed to obtain glass products. The melting temperature is 1400℃-1600℃, and the melting time is 6-10 h. The preheating temperature of the stainless steel mold is 300℃-450℃; the annealing temperature is 400℃-500℃, and the annealing time is 3-6 h.
[0049] Weigh out the graphite particles, silica particles, dispersant, and deionized water according to the formula. First, add the silica particles to the deionized water and pre-disperse them for 20 min under mechanical stirring. Then add the graphite particles and continue stirring for 30 min. Subsequently, add the dispersant to adjust the pH. If necessary, use ultrasonic dispersion for 10 min to obtain a uniform slurry. Use a rotational viscometer to measure the slurry viscosity and a pH meter to measure the slurry pH value.
[0050] A slurry is sprayed onto one side of a glass substrate. Specifically, the slurry is uniformly sprayed onto one surface of the glass substrate, leaving the other surface unsprayed. After spraying, the substrate is dried at 90°C for 30 minutes to obtain a glass substrate with a composite functional layer. Unless otherwise specified, the average dry weight coverage of the composite functional layer is controlled at 0.9 g / m², and the average thickness is approximately 2.5 μm-3.5 μm.
[0051] Glass substrates with composite functional layers are neatly stacked in groups of 10. Adjacent glass substrates are stacked such that the composite functional surface of one substrate contacts the non-functional surface of the other, forming a glass stack. Silicon carbide pads are placed at the top and bottom of the stack. The stack is then placed in a box furnace and crystallized according to the following procedure: Nucleation stage: Increase the temperature to 580℃ at a rate of 3℃ / min and hold for 3 hours; Crystallization stage: Increase the temperature to 720℃ at a rate of 2℃ / min and hold for 1 h; It was then cooled to room temperature at a rate of 5°C / min.
[0052] After crystallization, the glass stack is separated to obtain single-piece glass-ceramic products. Depending on the requirements of different embodiments, further CNC machining, double-sided polishing, and ion exchange strengthening treatment can be performed. The ion exchange treatment uses a mixed molten salt bath of sodium nitrate / potassium nitrate / lithium nitrate, and is carried out at 480°C for 4 hours.
[0053] The performance evaluation methods for microcrystalline glass products and slurries include the following indicators: Warpage: The ratio of the maximum warpage height to the length of the ceramicized glass slide; Five-point crystallinity difference: the relative standard deviation of crystallinity at the four corners and center of the glass slide; Separation force: The minimum vertical tensile force required for separation between adjacent glass sheets after ceramization, used to quantitatively evaluate the demolding effect of composite functional layers; Slurry pH value: measured directly using a pH meter; Viscosity: The dynamic viscosity value is calculated by measuring the resistance of the slurry to the rotating rotor at a specific rotation speed using a rotational viscometer.
[0054] Example 1
[0055] Low-warpage glass-ceramics are prepared according to the following steps: Step 1: A mixture of 72.15% SiO2, 2.63% Al2O3, 2.31% P2O5, 14.22% Li2O, 7.48% ZrO2, 0.5% Na2O, 0.2% CaO, 0.1% Sb2O3, and 0.41% SnO2 was thoroughly mixed and melted at 1500℃ for 8 hours. The mixture was then cast and annealed at 480℃ for 4 hours to obtain a glass substrate. The glass substrate was cut and shaped into 150 mm × 75 mm × 0.8 mm samples for later use. Step 2: Coating. A composite functional layer is formed on the upper surface of the glass substrate by spraying. The coating uniformity deviation is controlled to be ≤5%. After drying, a stable structure is formed. The slurry composition during spraying is graphite particles, silica particles, dispersant, and the balance water. The silica particles account for 25 wt% of the total slurry content, the graphite particles account for 10 wt% of the total slurry content, and the dispersant is sodium hydroxide accounting for 0.5% of the total slurry mass. Step 3: Crystallization. The glass stack is placed in a box furnace and heated to 540℃-620℃ at a rate of 1℃ / min-5℃ / min, and held for 1h-10h for nucleation. Then, the temperature is increased to 640℃-780℃ at a rate of 1℃ / min-3℃ / min, and held for 0.5h-5h for crystallization. Finally, the temperature is cooled to room temperature at a rate of 3℃ / min-10℃ / min to complete the crystallization process and obtain the glass microcrystalline glass stack.
[0056] Step 4: Destacking and processing. Due to the isolation effect of the composite functional layer, there is no adhesion between the glass sheets in the glass stack, and they can be separated directly by manual or mechanical means. The glass is then CNC machined and polished to obtain low-warpage glass products. Further, the obtained glass products undergo ion exchange treatment and are then repolished to obtain high-strength, low-warpage glass products.
[0057] Examples 2-6 and Comparative Examples 1-10 The difference between Examples 2-6 and Comparative Examples 1-5 and Example 1 is the different content of silica and graphite in the slurry in step 2. The difference between Comparative Examples 6-10 and Example 1 is the different thickness of the composite functional layer or the different types of silica and graphite, as well as the warpage and five-point crystallization differences of the final product. See Tables 1 and 2 for details.
[0058] The XRD test results of the final glass-ceramics prepared in Examples 1 and 6 are shown in the figure. Figure 1 and Figure 2 As shown. Physical images of the final glass-ceramics obtained in Example 5, Comparative Examples 6 and 7 are shown below. Figures 3-5 As shown, by Figure 3-5 It is evident that the microcrystalline glass prepared using the technical solution required by this invention has no obvious warping, while the microcrystalline glass prepared in Comparative Examples 6 and 7 has obvious or even severe warping, making it unsuitable for industrial application.
[0059] Table 1. Slurry formulations and related performance results for Examples 1-3 and Comparative Examples 1-3.
[0060] Table 2. Slurry formulations and related performance results for Examples 4-6 and Comparative Examples 4-10.
Claims
1. A method for preparing low-warpage microcrystalline glass, characterized in that, Includes the following steps: Step 1: Melting. Weigh out the following components by mass fraction: SiO2 60-75%, Al2O3 2-5.5%, P2O5 2-5%, Li2O 10-18%, ZrO2 4-10%, CaO 0-1%, Na2O 0-1.5%, Sb2O3 0.02-0.6%, SnO2 0.2-0.6%. Mix them evenly, melt them into a mold, and then anneal them to obtain a glass substrate. Step 2: Coating. A composite functional layer is formed on at least one main surface of the glass substrate obtained in Step 1. The composite functional layer is formed on the main surface of the glass substrate by spraying, and the coating uniformity deviation is controlled to be ≤5%. After drying, a composite functional layer with a thickness of 1-5.5µm is formed. The composite functional layer is composed of graphite particles, silica particles and dispersant, wherein the mass ratio of graphite particles to silica particles is (2-6):5, the dispersant content is 0.249-2.59wt% of the total weight of the composite layer, the graphite particles are flake graphite particles, and the dispersant is sodium hydroxide and / or potassium hydroxide. Step 3: Crystallization. The glass substrates with composite functional layers obtained in Step 2 are stacked and placed in a box furnace. First, the temperature is increased to 540℃-620℃ at a rate of 1℃ / min-5℃ / min and held for 1h-10h for nucleation treatment. Then, the temperature is increased to 640℃-780℃ at a rate of 1℃ / min-3℃ / min and held for 0.5h-5h for crystallization treatment. Finally, the temperature is cooled to room temperature at a rate of 3℃ / min-10℃ / min to complete the crystallization treatment and obtain a stack of microcrystalline glass. Step 4: Destacking and processing: Manually or mechanically separate the glass stacks, and perform CNC machining and polishing to obtain low-warpage microcrystalline glass products.
2. The method for preparing low-warpage microcrystalline glass according to claim 1, characterized in that, The graphite particles have an average particle size of 1μm-10μm and a graphitization degree of not less than 85%; the silica particles are amorphous silica particles with a particle size of 100 nm-5μm; and the dispersant is sodium hydroxide and / or potassium hydroxide.
3. The method for preparing low-warpage microcrystalline glass according to claim 1, characterized in that, It also includes step 5: subjecting the obtained glass products to ion exchange treatment and then polishing them.
4. A low-warpage microcrystalline glass, characterized in that, The product is prepared by any one of the methods described in claims 1-3, and has a warpage ≤1.5 μm / mm and a five-point crystallinity difference ≤5%.
5. The low-warpage microcrystalline glass according to claim 4, characterized in that, The low-warp microcrystalline glass contains lithium disilicate, or lithium disilicate and lithium feldspar, and the content of the crystalline phase accounts for 60%-90% of the weight of the microcrystalline glass.
6. A cover glass, characterized in that, The cover glass comprises low-warp microcrystalline glass as described in any one of claims 4-5.
7. A glass device, characterized in that, The glass device comprises low-warp microcrystalline glass as described in any one of claims 4-5.
8. An electronic device, characterized in that, The electronic device comprises low-warp microcrystalline glass as described in any one of claims 4-5.
Citation Information
Patent Citations
Microcrystalline glass brazing filler metal for ceramic connection, preparation method of glass ceramic brazing filler metal and ceramic connection method
CN113880426A
Preparation method of low-warpage tempered glass
CN120535214A